The Role of Callous-Unemotional Traits on Adolescent Positive and Negative Emotional Reactivity: A Longitudinal Community-Based Study - Truedsson, Erik; Fawcett, Christine; Wesevich, Victoria; Gredebäck, Gustaf; Wåhlstedt, Cecilia (Frontiers in Psychology, 2019)
Callous-unemotional (CU) traits are associated with lower emotional reactivity in adolescents. However, since previous studies have focused mainly on reactivity to negative stimuli, it is unclear whether reactivity to positive stimuli is also affected. Further, few studies have addressed the link between CU traits and emotional reactivity in longitudinal community samples, which is important for determining its generalizability and developmental course. In the current study, pupil dilation and self-ratings of arousal and valence were assessed in 100 adolescents (15-17 years) from a community sample, while viewing images with negative and positive valence from the International Affective Pictures System (IAPS). Behavioral traits (CU) were assessed concurrently, as well as at ages 12-15, and 8-9 (subsample, n = 68, low levels of prosocial behavior were used as a proxy for CU traits). The results demonstrate that CU traits assessed at ages 12-15 and 8-9 predicted less pupil dilation to both positive and negative images at ages 15-17. Further, CU traits at ages 12-15 and concurrently were associated with less negative valence ratings for negative images and concurrently to less positive valence ratings for positive images. The current findings demonstrate that CU traits are related to lower emotional reactivity to both negative and positive stimuli in adolescents from a community sample.